Pengukuran Tingkat Kematangan Menggunakan COBIT 5 Domain EDM (Evaluate, Direct And Monitor) Pada Website Prodi Sistem Informasi Universitas Hindu Indonesia - I Made Wira Satria Gunarta; Kadek Oky Sanjaya; I Kadek Noppi Adi Jaya (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2024)
The Information Systems Study Programme website is a feature of utilizing information technology as a software service in the education sector and provides information about the Information Studies Programme. Information system audits involve collecting and evaluating evidence to ascertain the protection of computer system assets. COBIT serves as a widely used framework during audits. The EDM domain oversees policymaking, monitoring, and ensuring organizational goals are met through appropriate IT usage. Data collection methods include interviews, observations, and questionnaire dissemination. Analysis methods comprise current maturity, expected maturity levels, and gap analysis. According to the analysis, the website's maturity level is at Level 4: Predictable Process. The gap level on the website is 0.8 for EDM 01 and 0.7 for EDM 04. Further research is recommended using other domains focusing on management to comprehensively understand maturity levels.